2017
DOI: 10.1039/c7cp05265k
|View full text |Cite
|
Sign up to set email alerts
|

The nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations

Abstract: Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
4
38
0
Order By: Relevance
“…N–H stretching modes at 3201 cm −1 in MAPbI 3 redshifts to 3114 cm −1 in 10% w/w PbSe:CH 3 NH 3 PbI 3 films due to the electrostatic attraction between Se 2− and cationic CH 3 NH 3 + . Our IR study follows the observation that Se interacts with H in N–H and retard stretching modes of N–H . Also, significant band broadening is witnessed on N–H stretch in 10% w/w PbSe:MAPbI 3 , relative to the peak of N–H stretch in MAPbI 3 , matching the pattern of strong electrostatic interaction .…”
supporting
confidence: 82%
“…N–H stretching modes at 3201 cm −1 in MAPbI 3 redshifts to 3114 cm −1 in 10% w/w PbSe:CH 3 NH 3 PbI 3 films due to the electrostatic attraction between Se 2− and cationic CH 3 NH 3 + . Our IR study follows the observation that Se interacts with H in N–H and retard stretching modes of N–H . Also, significant band broadening is witnessed on N–H stretch in 10% w/w PbSe:MAPbI 3 , relative to the peak of N–H stretch in MAPbI 3 , matching the pattern of strong electrostatic interaction .…”
supporting
confidence: 82%
“…The entropic penalty of the supramolecular polymerization of c-SeBTA (DS e = À97 J mole À1 K À1 ) was comparable to that of c-SBTA 30,36 (DS e = À102.6 J mole À1 K À1 ), instead, and we speculate similar ordering between the homopolymers of c-SeBTA and c-SBTA. We rationalize these thermodynamic parameters with an increased dipole-dipole and charge transfer character of the diffuse Se-NH hydrogen bond, 21,37 which ultimately affords the increased thermal stability of the supramolecular polymers of c-SeBTA (more favorable DH e and very similar DS e compared to c-SBTA). Interestingly, the nucleation penalty, and hence cooperativity, of the supramolecular polymers of c-SBTA and c-SeBTA were comparable (s = 1.9 Â 10 À3 for c-SBTA, 30,36 and 3 Â 10 À4 for c-SeBTA).…”
mentioning
confidence: 85%
“…We compare its self-assembly behavior to that of OBTA/c-OBTA 20 and SBTA/c-SBTA. 21 The different nature of the selenoamide hydrogen bond is illustrated by our finding that c-SeBTA polymers have an increased stability towards thermal denaturation yet enhanced lability towards polar solventsinduced denaturation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The simulation of DPDS with the Dmδ-AlaD demonstrated that this organoselenium compound could access the active site making hydrophobic interactions with Arg205, Pro212 (alkyl and phenyl groups), Phe204 and Tyr201 (phenyl and phenyl moieties), besides interacting with Arg217 via H-bond (selenyl and guanidinyl groups [95,96]) (Fig. 4C).…”
Section: Organoselenium Molecular Docking Studymentioning
confidence: 99%